Peran Perempuan dalam Misi Pemeliharaan Perdamaian dan Keamanan Internasional - Hasan, Nurul Istiana; Kurnia Putra, Akbar (Uti Possidetis: Journal of International Law, 2020)
In many countries where peacekeeping missions are carried out, gender-based violence and conflict-related sexual violence occur in alarming numbers. Both civilians and fighters, women and children are the most victims in a conflict. Armed conflict becomes a traumatic experience for each individual who experiences it. Women peacekeepers representing the United Nations are in a State to help restore the trust of people experiencing post-conflict trauma. However, to date the number of women is still very low compared to men in the United Nations Peacekeeping Mission. The UN Charter mandates the Security Council to maintain international peace and security. The study discusses how women play a role in international peacekeeping and security missions as well as actions. This type of research is a normative juridical sourced in secondary data. The results of this study show that in all areas of peacekeeping, female peacekeepers have proven that they can perform the same role, by standards and in the same difficult conditions. Therefore, it is an operational imperative of the United Nations to recruit and maintain female peacekeeping forces. Â